INTENTIONS TO REDUCE FOOD WASTE IN YOGYAKARTA: THE INFLUENCE OF RESPONSIBILITY AWARENESS, NORMS, AND BEHAVIORAL CONTROL - Aryo Saputro Tugino; Budi Astuti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines household intentions to reduce food waste in the Special Region of Yogyakarta by testing the effects of awareness, personal responsibility, social norms, and perceived behavioral control within the TPB and NAM perspective. A cross sectional survey was administered to households in Yogyakarta using a structured questionnaire. Data were analyzed with descriptive statistics and multiple linear regression using SPSS to estimate both partial and simultaneous effects. Descriptive results indicate that intention to reduce food waste, awareness, personal responsibility, social norms, and perceived behavioral control are generally high, suggesting strong readiness for more sustainable food management practices. The regression model is significant with an F value of 53.266 and a p value below 0.001. The coefficient of determination is 0.448, meaning the four predictors explain 44.8 percent of the variance in intention. Each variable has a positive and significant partial effect with t values of 3.907 for awareness, 4.418 for responsibility, 4.048 for social norms, and 8.154 for perceived behavioral control. Perceived behavioral control is the most dominant predictor with a beta value of 0.390.